INFLUENCE OF RECRUITMENT PROCESS, COMPETENCE, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT PRIMO MICROPHONE BATAM - Dame Riaty Hutabarat; Habibuddin Nasution; Mira Yona; Meilani Putri Novita (CV. Radja Publika, 2026)
This study investigates the influence of the recruitment process, employee competence, and the work environment on employee performance at PT Primo Microphone Batam. The research is motivated by the critical role of human resource management in an audio equipment manufacturing company that requires high precision, productivity, and consistent product quality. A quantitative approach with a causal-associative design was employed, using the entire workforce of PT Primo Microphone Batam as the population, all of whom were included as respondents through a saturated sampling technique (n = 100). Data were collected using a structured Likert-scale questionnaire and analyzed through validity and reliability testing, classical assumption tests, and multiple linear regression. The results show that the recruitment process, competence, and work environment each have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 57.1% indicates that these three variables jointly explain 57.1% of the variance in employee performance, while the remaining 42.9% is influenced by other factors outside the model. These findings highlight the importance of implementing competency-based recruitment, strengthening competence development programs, and creating a conducive work environment as key strategies for improving employee performance and enhancing the company’s competitiveness.